2012
DOI: 10.1037/a0026070
|View full text |Cite
|
Sign up to set email alerts
|

Slow and steady wins the race: A randomized clinical trial of acceptance and commitment therapy targeting shame in substance use disorders.

Abstract: Objective Shame has long been seen as relevant to substance use disorders, but interventions have not been tested in randomized trials. This study examined a group-based intervention for shame based on the principles of acceptance and commitment therapy (ACT) in patients (N = 133; 61% female; M = 34 years old; 86% Caucasian) in a 28-day residential addictions treatment program. Method Consecutive cohort pairs were assigned in a pairwise random fashion to receive treatment as usual (TAU) or the ACT interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
233
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(248 citation statements)
references
References 63 publications
13
233
0
2
Order By: Relevance
“…Interventions are probably more efficient if they focus on members of a subgroup with consistently more sceptical views about professional sources of help who are more prone to underutilize available services. Initiatives that aim to increase service use by reducing (anticipated) shame about having a mental illness and by increasing perceived knowledge could consist of marketing campaigns addressing the general public (Jorm, 2012;Henderson et al 2013), of more focused programs using education-and contactbased approaches with target groups (Corrigan et al 2012), of selected or indicated prevention programmes for people at risk for mental illness (Compton, 2010;de Girolamo et al 2012;Yap & Jorm, 2012), or of more clinically oriented interventions among diagnosed individuals who have already entered the mental health service system (Yanos et al 2011;Luoma et al 2012;Corrigan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions are probably more efficient if they focus on members of a subgroup with consistently more sceptical views about professional sources of help who are more prone to underutilize available services. Initiatives that aim to increase service use by reducing (anticipated) shame about having a mental illness and by increasing perceived knowledge could consist of marketing campaigns addressing the general public (Jorm, 2012;Henderson et al 2013), of more focused programs using education-and contactbased approaches with target groups (Corrigan et al 2012), of selected or indicated prevention programmes for people at risk for mental illness (Compton, 2010;de Girolamo et al 2012;Yap & Jorm, 2012), or of more clinically oriented interventions among diagnosed individuals who have already entered the mental health service system (Yanos et al 2011;Luoma et al 2012;Corrigan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A randomised clinical trial investigated the role of a 6 hour Acceptance and Commitment Therapy (ACT; 35) workshop on self-stigma among problematic substance users (36). At a 4 month follow-up, when compared to treatment as usual, the ACT intervention resulted in reduced shame-proneness, fewer days of substance use, and higher treatment utilisation (36).…”
Section: Acceptance and Self-forgivenessmentioning
confidence: 99%
“…A randomised clinical trial investigated the role of a 6 hour Acceptance and Commitment Therapy (ACT; 35) workshop on self-stigma among problematic substance users (36). At a 4 month follow-up, when compared to treatment as usual, the ACT intervention resulted in reduced shame-proneness, fewer days of substance use, and higher treatment utilisation (36). Although the ACT intervention had multiple components, the reduction in shame-proneness (36), as well as self-stigma during the intervention (29), suggests that acceptance may effect reductions in shame-proneness and be relevant to the self-forgiveness process.…”
Section: Acceptance and Self-forgivenessmentioning
confidence: 99%
“…Collaboratively working with patients to set treatment goals can foster increased engagement and retention in treatment, 23 something particularly relevant in the context of treatment for SUD and PTSD where attrition from treatment is common. 24,25 There are several limitations of the present study that warrant attention. For example, the assessment of substance use goals was limited to two choices, abstinence or reduced use, and did not elicit additional information regarding reasons for choosing a particular goal.…”
Section: Discussionmentioning
confidence: 99%